Right and Left Inverted Lobar Lung Transplantation. Issue 6 (2nd April 2015) - Chen, F.; Miyamoto, E.; Takemoto, M.; Minakata, K.; Yamada, T.; Sato, M.; Aoyama, A.; Date, H.
<x xml:space="preserve">Abstract</x> Adult recipients frequently withdraw from living‐donor lobar lung transplantation because of the small size of donor grafts. The right lower lobe is 120% larger than the left lower lobe. We developed a novel surgical technique in which an inverted right lower lobe graft can be transplanted into the left thorax. The first patient was a 43‐year‐old woman with end‐stage idiopathic interstitial pneumonia. Her husband was the only eligible donor for living‐donor lobar lung transplantation. His right lower lobe was estimated to provide 45% of the recipient's predicted forced vital capacity, which would provide the borderline function required for living‐donor lobar lung transplantation. Since lung perfusion scintigraphy of the recipient showed a right‐to‐left ratio of 64:36, transplanting the right lower lobe graft into the left thorax and sparing the native right lung was considered the only treatment option. We simulated this procedure using three‐dimensional models produced by a three‐dimensional printer. In living‐donor lobar lung transplantation, all anastomoses were performed smoothly as planned preoperatively. Because of the initial success, this procedure was performed successfully in two additional patients. This procedure enables larger grafts to be transplanted, potentially solving critical size matching problems in living‐donor lobar lung transplantation.